The relationship between individual and social factors with career development at UMLand Berhad, Southern Region - Sreedharan, Shubashini (2014)
This study is focused on identifying the relationship between the employees’ career planning, social learning, family’s needs and expectations, and gender equity with career development in UMLand, southern region. The researcher also intends to determine the difference in perception on career development, based on gender, age, level of education, job position, functional discipline of job, years of experience and years of service in the current company. A total of 159 employees were included in this parameter of study. The respondents were working across a wide spectrum of jobs which ranged from managerial functions to non-executive duties. The researcher used the total population survey method as the sampling method. Sources of data for this research are gathered through questionnaires and secondary data through library research, journals, company documents etc. Data was analysed using the SPSS 16.0 software and using statistical method (t-Test, Anova, Pearson Correlation and Multiple Regression) to answer the objectives of the study. t-Test and Anova showed that there no significant relationship between age and gender with career development while there is a relationship between level of education, job position, functional discipline of job, years of experience and years of service in the current company with career development in UMLand. Pearson Correlation showed that all four independent variables ie. career planning, social learning, family’s needs and expectations, and gender equity are significantly related with career development in UMLand. Meanwhile Multiple Regression method identified family’s needs and expectations to be the most dominant factor among the four that affects career development in UMLand